Spore germination and life cycle of paku kidang (Dicksonia blumei Moore) on the various growing media - SRI HARTINI (Biodiversitas Journal of Biological Diversity, 2006)
Dicksonia blumei Moore belongs to Dicksoniaceae (fern family). This plant has been used as ornamental plant, handy craft, traditional medicine particularly for styptic and growing medium for orchids and aroids. To obtain the material, people tended to exploit it in its natural habitat and neglected its sustainable. On the other hand current knowledge of its cultivation as well as conservation is very limited. As a result, this species become rare in the wild and its population decreased gradually. An experiment in spore germination of this species had been carried out at the Bogor Botanic Gardens nursery using five growing media viz. chopping root of tree fern (Cyathea contaminans), Calliandra macrophylla compost, chopping root of birdâ€™s nest fern (Asplenium nidus), bamboo (Dendrocalamus giganteus) leaf compost and sandy mud. Parameters used were the best medium for spore germination and sporelings growth, life cycle of spore until young sporophyte were obtained. The result showed that the best medium for spore germination of D. blumei was chopping of tree fern root and bamboo leaf compost was worse. The life cycle consists of cell differentiated, young prothallus, mature prothallus, and young sporophyte phases, which took 10-36 weeks. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: germination, media, spore, Dicksonia blumei Moore, Bogor Botanic Gardens.